Penyelesaian Sengketa Lahan Fasilitas Umum Antara Developer Dengan Warga Perumahan Waru Surya Indah Sukoharjo - Aprilliando, Pito; , Darsono, S.H., M.Hum (2016)
There is a land dispute between the Public Facilities Housing Developers with citizens Waru Surya Indah Sukoharjo. This study aims to determine the settlement of the land dispute between the developer of public facilities by residents Housing Waru Surya Indah Sukoharjo and to identify obstacles in resolving the land dispute between the developer of public facilities by residents Housing Waru Surya Indah Sukoharjo. Methods using descriptive sociological approach. Using primary data types and data sekunder. Teknik used data collection through questionnaires, interviews, observation, and literature study. By using qualitative data analysis. The results showed that the resolution of the dispute initially through mediation because mediation is not successful it is done through the courts and won by the citizens and to the constraints faced by the citizens in resolving land disputes public facilities with the developer is due to the mismatch between the brochure or leafet existing implementation , due to delays in the communication between the developer with the citizens as consumers, and due to the difficulty to reach an agreement between the developer with the citizens of Housing Waru Surya Indah Sukoharjo as a consumer.